Lack of XAGE‐1b and NY‐ESO‐1 in metastatic lymph nodes may predict the potential survival of stage III melanoma patients. Issue 6 (20th January 2017) - Mori, Mariko; Funakoshi, Takeru; Kameyama, Kaori; Kawakami, Yutaka; Sato, Eiichi; Nakayama, Eiichi; Amagai, Masayuki; Tanese, Keiji
Abstract: The cancer–testis antigens (CTA) are a large family of tumor‐associated antigens expressed by a variety of cancer cells and primitive germ cells of the adult testis and placenta. These tumor‐restricted expressing patterns suggest that CTA would be ideal targets for tumor‐specific immunotherapy. XAGE‐1 is a CTA that was originally identified by computer‐based screening, and four transcription variants, XAGE‐1a, ‐1b, ‐1c and ‐1d, have been characterized to date. Although the presence of XAGE‐1 transcripts has been reported in various cancers, the expression of XAGE‐1b in melanoma has not been fully characterized. In this study, we performed immunohistochemical staining of XAGE‐1b together with NY‐ESO‐1, a well‐known CTA, in 113 melanoma samples obtained from 84 patients and evaluated their expression in tumor cells. The effects of expression on tumor progression and patient prognosis were analyzed. Both XAGE‐1b and NY‐ESO‐1 were expressed at high levels in lymph node metastasis and skin metastasis samples compared with the primary site ( P < 0.01 in XAGE‐1b and P < 0.05 in NY‐ESO‐1). In a subgroup analysis of 22 patients with stage III lymph node metastasis, overall survival was significantly higher in the XAGE‐1b and NY‐ESO‐1 double‐negative group than in the other groups ( P < 0.05). These results suggest that lack of XAGE‐1b and NY‐ESO‐1 expression could have a positive influence on clinical outcome in patients with melanoma.